Possibly preventable cardiac arrest in a morbidly obese patient - a comment on the 2015 ERC guidelines. Issue 1 (December 2016) - Hans, Felix; Hoeren, Claudia; Kellmeyer, Phillipp; Hohloch, Lisa; Busch, Hans-Jörg; Bayer, Jörg
Abstract Background The incidence of overweight and obesity has been steadily on the rise and has reached epidemic proportions in various countries and this represents a well-known major health problem. Nevertheless, current guidelines for resuscitation do not include special sequences of action in this subset of patients. The aim of this letter is to bring this controversy into focus and to suggest alterations of the known standard cardiopulmonary resuscitation in the obese. Case presentation An obese patient weighing 272 kg fell to the floor, afterwards being unable to get up again. Thus, emergency services were called for assistance. There were no signs or symptoms signifying that the person had been harmed in consequence of the fall. Only when brought into a supine position the patient suffered an immediate cardiac arrest. Cardiopulmonary resuscitation was performed but there was no return of a stable spontaneous circulation until the patient was brought into a full lateral position. In spite of immediate emergency care the patient ultimately suffered a lethal hypoxic brain damage. Conclusion A full lateral position should be considered in obese patients having a cardiac arrest as it might help to re-establish stable circulatory conditions.